HUBUNGAN DURASI PENGGUNAAN GADGET DENGAN KUALITAS KETAJAMAN PENGLIHATAN PADA ANAK USIA REMAJA AWAL DI SMP NEGERI 2 SAMARINDA - Kalsum, Umi; Salwanah, Chiara Dewi; Noorma, Nilam; Arming, Andi Lis G. (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Sharp vision is an ability of the eye or the refractive power of the eye to see an object. This study aims to determine the relationship between the duration of gadget use and the quality of visual acuity in early adolescent children at SMPN 2 Samarinda. The method of this study was a quantitative research method with the type of analytical study research and cross sectional research design The population in this study was all 7th and 8th grade students at SMPN 2 Samarinda which amounted to 689 people with a sample of 97 respondents where the sampling method used was probability sampling with a simple random sampling technique. The data collection technique was carried out by distributing questionnaires to respondents and conducting eye vision examinations on respondents. The data analysis technique used univariate analysis with frequency distribution and bivariate analysis using the Chi-square Test. Hypothesis test results with the Chi-Square Test obtained a value of 0,038 (pValue = 0,05) so that there was a relationship between the duration of gadget use and the quality of visual acuity in early adolescent children at SMP (Junior High School) 2 Samarinda. It is hope that every school will hold regular eye examinations. Keywords: Duratio, Gadget, Visual acuity